Effect of exogenous glutathione in medium fertilization to improve blastocyst rates of bovine embryos - E Triwulanningsih; P Situmorang; I-G Putu; T Sugiarti; A.M Lubis; D.A Kusumaningrum; W Caroline; R.G Sianturi (Indonesian Center for Animal Research and Development (ICARD), 2002)
Glutathione (C10H17N3O6S) is a tripeptide (γ-Glu-Cys-Gly) widespread in living organism. Glutathione (GSH) at the 5 mM concentration increased the motility and fertility of frozen-thawed sperm. Intracellulair glutathione improved the cleavage rate and embryo development to the blastocyst rate. Research on in vitro embryos production through the implementation of GSH during IVF (in vitro fertilization) on embryo development has been conducted at the Laboratorium Reproductive of Physiology, Research Institute for Animal Production. Ovaries of beef cattle as source of oocytes were collected from the slaughterhouse in a thermo flask with 350C PBS as medium and transported to the laboratory. The oocytes were fertilized in vitro with selected motile sperm using Percoll gradient (90 and 45%). Ten COCs (cumulus oocytes complexes) were transfered to 44 μl of fertilization medium (mTALP) was performed with either 0; 0.25; 0.50; 0.75 and 1.00 mM of glutathione as treatment A, B, C, D and E respectively, and inseminated with 2 μl of capacitated sperm and added 2 μl of heparin and 2 μl of PHE (consisting of 20 μM penicillamine, 10 μM hypotaurine, 1 μM epinephrine). Incubation between sperm and oocytes in the 5% CO2 incubator and RH 90% in fertilization media (TALP) for 20 hours. All zygotes were cultured in modification of CR1aa medium up to blastocyst and were fed serum 5 μl/50μl medium on day 6. Results of this experiment showed that the effect of concentration of glutathione (0, 0.25; 0.50; 0.75 and 1.00 mM) on fertilization medium to the percentage of cleavage rates were 69.35 + 29.40; 79.07 + 13.17; 67.88 + 10.65; 98.10 + 3.30 and 82.62 + 24.19% not significant different (P>0.05) among treatments A, B, C, D dan E respectively.The precentages of morula and blastocyst for treatment D were 50.45 + 42.64% and 31.28 + 24.28%; while 36.55 + 24.13% and 17.74 + 17.86% for treatment E respectively. Key words: Glutathione, in vitro fertilization, oocytes, cleavage